Small Data, Big Disruptions - Schwirn, Martin (Ascent Audio, 2021)
An organization's future success depends on their decision makers' ability to anticipate changes and disruptions in the marketplace. But how do you get information about tomorrow today? How can your decisions today account for tomorrow's uncertainties? Small Data, Big Disruptions presents a tool kit to foresee coming changes: - Understand why big data will not help you with understanding tomorrow's disruptions. The future starts with small data-first. - Learn the proven four-step process to capture small data that help envision the future. - See examples of how the process anticipated major disruptions. - Implement the process in your organization and learn how to initiate meaningful actions. This book provides the information you need to anticipate the future, understand tomorrow's market dynamics, and make the necessary decisions to meet the future on your terms. Small Data, Big Disruptions lets you exploit the period between the moment you could know about emerging disruptions and the moment most everybody will know about it. It's the difference between being ahead of the curve and struggling to catch up.
Online resource; Title from title page (viewed April 15, 2021)
Keywords: Audiobooks; Livres audio